Supply Chain Resilience and Firm Performance: A Comparative Analysis of Manufacturing Companies in Switzerland - Meier, Jonas (European Journal of Business and Strategic Management, 2024)
Purpose: The aim of the study was to analyze the supply chain resilience and firm performance: a comparative analysis of manufacturing companies in Switzerland. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study underscores the importance of proactive measures like contingency planning and supplier diversification. It also emphasizes the need for continual adaptation of resilience strategies to changing market conditions. Overall, the research highlights the critical role of supply chain resilience in enhancing firm performance and competitiveness in Switzerland's business landscape. Unique Contribution to Theory, Practice and Policy: Resource-based view (RBV), institutional theory & transaction cost economics (TCE) may be used to anchor future studies on analyze the supply chain resilience and firm performance: a comparative analysis of manufacturing companies in Switzerland. Spanish manufacturing companies should prioritize investments in technological capabilities, such as advanced analytics and real-time monitoring systems, to enhance their ability to detect and respond to disruptions in the supply chain promptly. Policymakers should focus on creating an enabling environment for innovation and digitalization within the manufacturing sector through incentives, subsidies, and supportive regulatory frameworks.